Dilemmas and theoretical exploration of China’s rural land property rights system reform - Laiyou, Zhou; Jiawei, Luo (Frontiers in Sustainable Food Systems, 2023)
Introduction：The property rights system, as the core component of the land system, is related to the long-term stability of the country, the well-being of farmers and the realization of the value of ecological products. The reform of China's rural land property rights system has long been controversial. This paper compares the main historical lines of the reform of the rural land property rights system since the founding of New China, notes its dilemmas, and theoretically explores its development.Methods：This article adopted literature analysis method(LAT), Sorted out the historical mainline of rural land property rights system reform since the establishment of the People's Republic of China, proposed its reform path.Results：The paper finds that the two main difficulties of the reform are the weakening of collective property rights, leading to the disintegration of rural public services, and the refinement of farmers' property rights, leading to an increase in agricultural operation costs. These issues lead to extremely high transaction costs in the process of agricultural production and operation, making agricultural production a worthless business activity.Discussion：this paper argues that a complete market structure is a "unified" market structure that includes the government and the market, in which the government plays the role of defining property rights and reducing transaction costs.